2013
DOI: 10.1017/s0033291713002808
|View full text |Cite
|
Sign up to set email alerts
|

P300 waveform and dopamine transporter availability: a controlled EEG and SPECT study in medication-naive patients with schizophrenia and a meta-analysis

Abstract: Our findings suggest the P300 ERP is not altered in the early stages of schizophrenia before medication is introduced, and the DAT availability does not influence the P300 ERP amplitude or latency. P300 ERP amplitude reduction could be an indicator of the progression of illness and chronicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
1
12
0
1
Order By: Relevance
“…Progression of illness may also play an important role. 11 The present study has several limitations. First, the sample size is relatively small; a greater number of participants is required to improve the power of the current results.…”
Section: Discussionmentioning
confidence: 83%
“…Progression of illness may also play an important role. 11 The present study has several limitations. First, the sample size is relatively small; a greater number of participants is required to improve the power of the current results.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies showed that high frequency magnetic stimulation increases anterior brain glutamate levels, in some cases with a left lateralization [ 29 32 ]. It is also known that dopamine modulation can influence both task performance testing and also event related potentials [ 33 , 34 ]. ERP latencies and amplitudes can be influenced by dopaminergic function, impacting cognitive speed processing and also neural resources magnitude allocation to a specific task.…”
Section: Discussionmentioning
confidence: 99%
“…To answer this question, we took the results from a recent schizophrenia genetic association meta-analysis by the Psychiatric Genomics Consortium (PGC), which discovered 128 independent genetic variants in 108 genomic loci associated with schizophrenia (Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014), and tested them for association with the same 17 endophenotypes described above. Many of these endophenotypes have demonstrated substantial construct validity as endophenotypes for schizophrenia (Iacono et al 2016); others less so, but nevertheless have been associated with schizophrenia, found to be heritable in twin studies, and show deviation in schizophrenia patient first-degree relatives (Fukushima et al 1988; Braff et al 1992; Iacono et al 1999; Hong et al 2012; Kam et al 2013; Chen et al 2014; Narayanan et al 2014; Qiu et al 2014). The only two endophenotypes that have not been linked to schizophrenia are our measures of affectively modulated startle (Iacono et al 2016).…”
Section: Introductionmentioning
confidence: 99%